Endotoxin in concentrated coarse and fine ambient particles induces acute systemic inflammation in controlled human exposures. Issue 11 (16th August 2013) - Behbod, Behrooz; Urch, Bruce; Speck, Mary; Scott, James A; Liu, Ling; Poon, Raymond; Coull, Brent; Schwartz, Joel; Koutrakis, Petros; Silverman, Frances; Gold, Diane R
Abstract : Background: Knowledge of the inhalable particulate matter components responsible for health effects is important for developing targeted regulation. Objectives: In a double-blind randomised cross-over trial of controlled human exposures to concentrated ambient particles (CAPs) and their endotoxin and (1→3)-β-D-glucan components, we evaluated acute inflammatory responses. Methods: 35 healthy adults were exposed to five 130-min exposures at rest: (1) fine CAPs (∼250 µg/m 3 ); (2) coarse CAPs (∼200 µg/m 3 ); (3) second coarse CAPs (∼200 µg/m 3 ); (4) filtered air; and (5) medical air. Induced sputum cell counts were measured at screening and 24 h postexposure. Venous blood total leucocytes, neutrophils, interleukin-6 and high-sensitivity C reactive protein (CRP) were measured pre-exposure, 3 and 24 h postexposure. Results: Relative to filtered air, an increase in blood leucocytes 24 h (but not 3 h) postexposure was significantly associated with coarse (estimate=0.44×10 9  cells/L (95% CI 0.01 to 0.88); n=132) and fine CAPs (0.68×10 9  cells /L (95% CI 0.19 to 1.17); n=132), but not medical air. Similar associations were found with neutrophil responses. An interquartile increase in endotoxin (5.4 ng/m 3 ) was significantly associated with increased blood leucocytes 3 h postexposure (0.27×10 9  cells/L (95% CI 0.03 to 0.51); n=98) and 24 h postexposure (0.37×10 9  cells/L (95% CI 0.12 to 0.63); n=98). This endotoxin effect did not differ by particle size. There were no associations with glucan concentrations or interleukin-6, CRP or sputum responses. Conclusions: In healthy adults, controlled coarse and fine ambient particle exposures independently induced acute systemic inflammatory responses. Endotoxin contributes to the inflammatory role of particle air pollution.